ANALISIS DEBT TO EQUITY RATIO DALAM HUBUNGANNYA DENGAN RENTABILITAS MODAL SENDIRI PADA PT. TELEKOMUNIKASI INDONESIA Tbk. - Clara Irga Putri Pratama; Wahyuningsih Ningsih; UU Suparman (Jurnal Ekonomi Dan Bisnis, 2017)
This research was entitled "Analysis Debt to Equity Ratio in Relation to Return on Equity at PT.Telekomunikasi Indonesia Tbk". The purpose of this study was to find out how the relation of Debt to Equity Ratio with Return On Equity of PT. Telekomunikasi Indonesia Tbk. The method used in this research was descriptive analysis method. Data collection techniques used documentation study and library research. The kind of data used is documentary, with secondarydata source was obtained from the official website PT. Telekomunikasi Indonesia Tbk. Data processingtechnique used is the analysis of data that included data reduction, display data and conclusiondrawning/verification. The results of this research showed that the Debt to Equity Ratio is positively related to theReturn On Equity at PT. Telekomunikasi Indonesia Tbk.